Gene alterations involving the CRLF2‐JAK pathway and recurrent gene deletions in Down syndrome‐associated acute lymphoblastic leukemia in Japan. Issue 11 (16th July 2014) - Hanada, Isamu; Terui, Kiminori; Ikeda, Fumika; Toki, Tsutomu; Kanezaki, Rika; Sato, Tomohiko; Kamio, Takuya; Kudo, Ko; Sasaki, Shinya; Takahashi, Yoshihiro; Hayashi, Yasuhide; Inukai, Takeshi; et al.
<x xml:space="preserve">Abstract</x> In Western countries, gene alterations involving the CRLF2‐JAK signaling pathway are identified in approximately 50–60% of patients with Down syndrome‐associated acute lymphoblastic leukemia (DS‐ALL), and this pathway is considered a potential therapeutic target. The frequency of BTG1 deletions in DS‐ALL is controversial. IKZF1 deletions, found in 20–30% of DS‐ALL patients, are associated with a poor outcome and EBF1 deletions are very rare (∼2%). We analyzed 38 patients to determine the frequencies and clinical implications of CRLF2‐JAK pathway genetic alterations and recurrent gene deletions in Japanese DS‐ALL patients. We confirmed a high incidence of P2RY8‐CRLF2 (29%) and JAK2 mutations (16%), though the frequency of P2RY8‐CRLF2 was slightly lower than that in Western countries (∼50%). BTG1 deletions were common in our cohort (25%). IKZF1 deletions were detected in 25% of patients and associated with shorter overall survival (OS). EBF1 deletions were found at an unexpectedly high frequency (16%), and at a significantly higher level in P2RY8‐CRLF2‐positive patients than in P2RY8‐CRLF2‐negative patients (44% vs. 4%, P = 0.015). Deletions of CDKN2A/B and PAX5 were common in P2RY8‐CRLF2‐negative patients (48 and 39%, respectively) but not in P2RY8‐CRLF2‐positive patients (11% each). Associations between these genetic alterations and clinical characteristics were not observed except for inferior OS in patients with IKZF1 deletions. These results suggest that differences exist between the genetic profiles of DS‐ALL patients in Japan and in Western countries, and that P2RY8‐CRLF2 and EBF1 deletions may cooperate in leukemogenesis in a subset of Japanese DS‐ALL patients. © 2014 Wiley Periodicals, Inc.